2021
DOI: 10.1038/s41416-020-01247-z
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations from the European Commission Initiative on Breast Cancer for multigene testing to guide the use of adjuvant chemotherapy in patients with early breast cancer, hormone receptor positive, HER-2 negative

Abstract: Background Predicting the risk of recurrence and response to chemotherapy in women with early breast cancer is crucial to optimise adjuvant treatment. Despite the common practice of using multigene tests to predict recurrence, existing recommendations are inconsistent. Our aim was to formulate healthcare recommendations for the question “Should multigene tests be used in women who have early invasive breast cancer, hormone receptor-positive, HER2-negative, to guide the use of adjuvant chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Although according to interim analysis of RxPONDER trial, the guideline recommends Oncotype DX for same subset of patients, however the interpretation of the results in premenopausal patients is complex 13 . The use of genomic signatures is recommended for this subset of patients by national and international clinical guidelines, i.e., St. Gallen Consensus Conference, European Society for Medical Oncology (ESMO), and American Society of Clinical Oncology 8 , 14 , 15 . However, the economic burden on patients makes clinicians hesitate to recommend genomic testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although according to interim analysis of RxPONDER trial, the guideline recommends Oncotype DX for same subset of patients, however the interpretation of the results in premenopausal patients is complex 13 . The use of genomic signatures is recommended for this subset of patients by national and international clinical guidelines, i.e., St. Gallen Consensus Conference, European Society for Medical Oncology (ESMO), and American Society of Clinical Oncology 8 , 14 , 15 . However, the economic burden on patients makes clinicians hesitate to recommend genomic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic analysis would be useful to make a decision in this subgroup of breast cancer patients with intermediate risk of prognostic clinical factors. Most of the breast cancer guidelines introduces to consider several genomic assays regarding the use of adjuvant chemotherapy 5 – 8 . MammaPrint (MMP), a 70-gene-signature‒based test is available for patients with HR + and minimal nodal involvement (N0-1).…”
Section: Introductionmentioning
confidence: 99%
“…These findings agree with other reports, for example, in the MINDACT study, 46.2% of the patients at clinical high risk were classified by MammaPrint as genomic low risk [ 5 ], while a Dutch study reported that MammaPrint classified 52.6% of clinical high-risk tumors as genomic low risk [ 18 ], supporting de-escalation. Recent guidelines suggest the use of the 70-gene signature only for women at high clinical risk [ 37 ]. However, although the agreement of clinical low risk with genomic data were high, 20% of cases displayed genomic high risk, implying that these patients would not receive the required therapy, and thus possibly resulting in their under-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On this point, Gomez HL et al reported that up to 70% of HR (+) and N0 ESBC patients with RS ≤ 25 may not need ACT [ 16 ]. Since the inconsistencies in risk prediction exist among the genome tests, the European Commission Initiative on Breast Cancer (ECIBC) Guidelines Development Group suggests the use of Oncotype DX for N0 breast cancer patients, and the use of MammaPrint for women at high clinical risk [ 9 ].…”
Section: Adjuvant Chemotherapy (Act)mentioning
confidence: 99%
“…However, some ESBC patients with ER+ and HER2− may have received unnecessary ACT, and those with a low risk of cancer recurrence may avoid ACT [ 8 ]. Thus, accurate prediction of the recurrence risk and response to ACT in patients with ESBC is crucial in order to optimize ACT [ 9 ].…”
Section: Introductionmentioning
confidence: 99%